Inorganic nitrite improves components of the metabolic syndrome independent of weight change in a murine model of obesity and insulin resistance. (25th June 2015) - Singamsetty, Srikanth; Watanabe, Yoshio; Guo, Lanping; Corey, Catherine; Wang, Yinna; Tejero, Jesus; McVerry, Bryan J.; Gladwin, Mark T.; Shiva, Sruti; O'Donnell, Christopher P.
Abstract : Key points: Nitrite acts as an endocrine source of bioavailable nitric oxide that can improve metabolic function. Exogenous administration of nitrite to genetically obese mice enhanced glucose tolerance and increased insulin sensitivity independent of weight change. Exogenous nitrite uncoupled mitochondrial respiration, decreased the generation of ATP, and increased phosphorylation of AMP‐activated protein kinase in skeletal muscle. The weight‐independent improvements in metabolic function from exogenous nitrite were comparable to rosiglitazone, suggesting the potential for therapeutic efficacy of nitrite in obese, insulin‐resistant, or diabetic patients. Abstract: Nitrite acts as an endocrine source of bioactive nitric oxide, impacting vascular reactivity, angiogenesis and cytoprotection. Nitrite has recently been shown to have a metabolic role although its effects and mechanisms of action in the obese insulin‐resistant state are unknown. We examined glucose tolerance and insulin secretion using the frequently sampled intravenous glucose tolerance test and insulin sensitivity using the hyperinsulinaemic euglycaemic clamp in obese male ob lep mice administered nitrite (100 mg kg −1  day −1 ) or saline (control) for 7 days and compared responses to the known insulin‐sensitizing effects of rosiglitazone (6 mg kg −1  day −1 ). Under weight‐matched conditions, nitrite lowered blood pressure relative to saline and rosiglitazone, whereas only rosiglitazone was effective at reducing hepatic glucose output and basal blood glucose. Both nitrite and rosiglitazone produced improvements, relative to saline, in glucose tolerance (12, 524 ± 602, 12, 811 ± 692 vs .14, 428 ± 335 mg (dl min) −1, respectively; P  < 0.05) and insulin sensitivity (8.6 ± 0.7, 7.9 ± 0.3  vs . 6.6 ± 0.5 mg kg −1  min −1, respectively; P  < 0.001), but there was no effect on insulin secretion. Nitrite exhibited an uncoupling of mitochondrial respiration and a decrease in ATP generation in muscle that was independent of mitochondrial biogenesis or activation of uncoupling proteins. There was no insulin‐stimulated phosphorylation of Akt, but nitrite increased the phosphorylation of AMP‐activated protein kinase. We conclude that nitrite improves two key components of the metabolic syndrome, blood pressure and insulin sensitivity, independent of weight and with effectiveness comparable to rosiglitazone.